Gloria Roll - Abd Kahar, Nur Aishah; Shamsudin, Nur Shakilah Natasha; Johan, Nur Aishah; Nasir, Mohd Fazli; Zainal Abidin, Amirah Diyanah; Rawi, Norazrin Hidayu (2017)
This business plan introduces "Gloria Roll," a partnership located at No. 63, Jalan Austin Heights 3/2, Taman Mount Austin, 81100 Johor Bahru, Johor. The business aims to sell its signature begedil burger to the target market, fulfilling customer demand, particularly among teenagers, burger enthusiasts, and those interested in trying novel food items. The main products offered are the begedil burger and the burger popia begedil. The business structure consists of six positions: Manager, Organization Executive, Marketing Executive, Financial Executive 1, Financial Executive 2, and Operation Executive. This plan encompasses the business administration, marketing, operational, and financial strategies. The purpose of this plan is also to estimate current year profit, project future company performance, and clearly outline the business vision, mission, objectives, and expectations, ensuring the team stays aligned with their entrepreneurial goals.